2020
DOI: 10.1186/s12889-020-09863-3
|View full text |Cite
|
Sign up to set email alerts
|

Meeting Indigenous youth where they are at: knowing and doing with 2SLGBTTQQIA and gender non-conforming Indigenous youth: a qualitative case study

Abstract: Background Research carried out in partnership with Indigenous youth at The Native Youth Sexual Health Network (NYSHN) demonstrates that Indigenous youth can (and do) develop and implement public health interventions amongst their peers and within their communities, when supported by non-youth allies and mentors. Methods Together, NYSHN and Well Living House researchers co-designed a qualitative case study to demonstrate and document how Indigenous youth can and do practice their own form of public health imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Forty-two articles [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ], from 38 unique studies, reported on aspects of Indigenous youth wellbeing in Canada. Our thematic analysis identified eight aspects of wellbeing for this population: basic resources for survival; safety and stability; relationships with others; culture and spirituality; knowledge, opportunities, and the future; identity; resilience and independence; and recreation and interests.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Forty-two articles [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ], from 38 unique studies, reported on aspects of Indigenous youth wellbeing in Canada. Our thematic analysis identified eight aspects of wellbeing for this population: basic resources for survival; safety and stability; relationships with others; culture and spirituality; knowledge, opportunities, and the future; identity; resilience and independence; and recreation and interests.…”
Section: Resultsmentioning
confidence: 99%
“…2SLGBTTQQIA = Two Spirit, lesbian, gay, bisexual, transgender, queer, questioning, intersex and allies. Two-spirit = Two-Spirit is used by and for Indigenous people as a way to relate to ourselves, our communities, and our spirits outside of a western colonial context; some people identify as having a spiritual balance between feminine and masculine energies [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations